REVITALIZATION OF LEADERSHIP IN DESIGNING MULTICULTURAL EDUCATION MANAGEMENT - Suryaman, Suryaman; Suharyanto, Suharyanto (Universitas Brawijaya, Indonesia, 2020)
This study aimed to describe leadership revitalization in designing educational management in the multicultural-based school. For this reason, this research used a qualitative design with a case-study approach conducted at SMA Selamat Pagi Indonesia, Batu, Indonesia. Data collection was done through documentation, interview, and observation techniques. The results showed that 1) SMA Selamat Pagi Indonesia was designed as a multicultural school or also referred to as Mini Indonesia since the recruitment of new students came from 19 provinces from all over Indonesia and consisted of followers of 6 major religions in Indonesia, and 2) The principal's leadership based on multiculturalism is indicated by several policies such as planting tolerance to students, creating study groups / working with diverse students, moving class learning systems, and providing entrepreneurship laboratories such as retail business division, tour, and travel division, show division, marketing division, and hotel division. Based on these findings, it is recommended for the school principal to care for multicultural values in schools to prepare for a better and broad-minded future of the graduates about the concept and application of multicultural life.